2011
DOI: 10.5146/tjpath.2011.01078
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of parathyroid adenomas and immunohistochemical analysis of pcna and ki-67 proliferation markers

Abstract: Objective: Parathyroid adenomas are the most common cause of primary hyperparathyroidism. Biological studies have shown that parathyroid adenomas are monoclonal proliferations. Up to date, five cell types have been identified in normal parathyroid tissues; chief cells, vacuolated chief cells, dark chief cells, oxyphil cells and transitional oxyphil cells. Most parathyroid adenomas are predominantly composed of chief cells.In this study, we aimed to indicate the relationship between the predominant cell type in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
1
11
0
3
Order By: Relevance
“…We found only one statistically significant correlation, between chief‐cell percentage and PTA weight ( P = 0.044). Most of the PTAs had a predominance of chief cells, consistent with earlier findings that chief‐cell PTAs are the most common type of PTA in PHPT . As chief cells secrete PTH, the higher proportion of this cell type would have been expected to lead to higher PTH levels and, consequently, higher blood calcium levels.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found only one statistically significant correlation, between chief‐cell percentage and PTA weight ( P = 0.044). Most of the PTAs had a predominance of chief cells, consistent with earlier findings that chief‐cell PTAs are the most common type of PTA in PHPT . As chief cells secrete PTH, the higher proportion of this cell type would have been expected to lead to higher PTH levels and, consequently, higher blood calcium levels.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the PTAs had a predominance of chief cells, consistent with earlier findings that chief-cell PTAs are the most common type of PTA in PHPT. 9,10,19 As chief cells secrete PTH, the higher proportion of this cell type would have been expected to lead to higher PTH levels and, consequently, higher blood calcium levels. However, no correlation was found between the proportion of chief cells and PTH or calcium levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry using anti-PTH antibodies has not been demonstrated to be useful in the diagnosis of PC [26]. Nevertheless, a proliferation index evaluated by the Ki-67 antibody higher than 5% is associated with a higher suspicion of malignancy and the risk of recurrence [27]. In the presented case, the mitotic index and proliferation index were three figures per ten high-power fields and 1%, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Studies revealed that the percentage of positively stained for Ki‐67 tumor cells is often associated with the clinical course of the disease . Parathyroid carcinomas showed higher Ki‐67 expression compared with adenomas and hyperplasias, however, there is an overlap between benign and malignant parathyroid lesions . World Health Organization guidelines suggest that patients with tumors with Ki‐67 counts greater than 2% to 3% should have a closer follow‐up because of an increased risk of malignancy…”
Section: Introductionmentioning
confidence: 99%